Tata Kelola Administrasi Desa Dalam Penyelenggaraan Pemerintahan di Era Otonomi Desa (Studi di Desa Buo Kecamatan Loloda Kabupaten Halmahera Barat) - Mais, Trisno; Rumapea, Patar; Rares, Joyce (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This research in order to acquire a thesis making a Bachelor degree Holders in the Faculty of social and Political Science Unsrat Manado. Moving on from the pre study done by researchers, that turns into alleged 1980 Village Administration Governance has not been applied in accordance with PERMENDAGRI NO. 32 in 2006 about the village Administration Guidelines. This is because there are some administration village of 1980 which have not been applied. Thus, the researchers saw a need to review and note the application of Administrative Governance at the village of 1980. This research uses qualitative research methods. The data collected from the stages of observation, in-depth interviews and documentation. On the collection of data on completed by using the guidelines of the interview, in which there are 9 informants interviewed. The informant is the ninth of which start from the head of Loloda (1) and (8) the village government. After being interviewed, the researchers analyzed the results of the interviews through several stages. Among the first with the collection of data is done through observation or interviews and then do record keeping and typing and editing as necessary, both the reduction of the holding against existing data selection, data analysis, summarize the sharpen as well as discard data that is not required, the third provides data and simplifying data have been obtained in order to facilitate research in the conclusion, the fourth withdrawal With drawl , verify their conclusions with a review the records or data acquired and analyzed as a result including brainstorm with friends colleagues and then take the conclusion. The results showed that the Administration's Governance is still not applied optimally as expected by PERMENDAGRI NO. 32 in 2006. The conclusion that can be drawn from the results of this research is that found there are several administration which has not been applied. Data book including the land of the village, the village's land book, appointment book, book, book the population mutation data recap of the population end of the month, BPD, book appointment book expedition BPD. So it is inferred that sub District and village Governments must still work together to realize the village administration governance better. Keyword: application of Administrative Governance,